Active Reflectors: Possible Solutions Based on Reflectarrays and Fresnel Reflectors. (16th March 2009) - Cabria, Lorena; García, José Ángel; Gutiérrez-Ríos, Julio; Tazón, Antonio; Vassal'lo, Juan
Abstract : An overview about some of the recent Spanish developments on active reflectors is presented. In the first part, a novel beamsteering active reflectarray is deeply studied. It is based on implementing in each elementary radiator an IQ modulator structure, in which amplitude and phase control of the scattered field is achieved. Finally, a special effort is made in offering solutions to overcome the active antenna integration problems. In the second part, the active concept is firstly extended to Fresnel reflectors. Thanks to the development of a proper simulator, this special structure can be easily analysed. This simulator allows the study of performance of this kind of reflectors and, applying evolutionary algorithms, to find optimal configurations of reflector in accordance with the given specifications for the conformal radiation pattern.